International tourism demand in Malaysia: evidence from panel data analysis / Aswad Kusni - Kusni, Aswad (2014)
Most of the researchers agree that tourism is an economic activity generated in the most of the countries around the globe; including Malaysia. Yet, measuring tourism activity in Malaysia is not an easy task, particularly at local and international level. The study on tourism demand is restricted due to limited access of data (times series or panel data), and methodology that varies across the philosophies and academic background of the researchers. However, most tourism demand studies focus to investigate the crucial factors that determine number of international tourist. The purpose of this study is to investigate the significance influence of selected economic and non-economic factors in determining international tourist arrivals from ASEAN and OECD countries to Malaysia. The sample period for this study ranges from 1995 to 2009. The data are analysed by using the panel data econometric technique; the fixed-/random effects model. The results of the study indicate that the income, substitute price of tourism in Singapore and exchange rate are statistically significant in determining international tourist arrivals from ASEAN and OECD countries to Malaysia. In addition, the words-of-mouth effect is found to be significant in influencing future tourists. The results of the study have determined several policy implications; firstly, the policy makers need to monitor and understand the price aspect closely to make sure that the price of tourism in Malaysia is competitive. Secondly, income is found to be an important factor in determining tourism demand; therefore, it is important for the policy makers and tourism agencies to deliver quality goods and services in attracting and attaining more tourists from ASEAN and OECD countries. Thirdly, it is recommended that the policy makers to promote domestic tourism products. Fourthly, the establishment of smart partnership program and alliance between the competing destinations needs to be implemented for the future economic development. Fifthly, the external effect needs to be considered in tourism study as history of several incidents which caused tremendous fall in the international tourist arrivals show how important the external effect towards tourism. Lastly, the development of tourism demand must be taken into consideration by the policy makers in achieving their target. Therefore, large portion of budget and attention must be given to the tourism sectors in order that the crucial determinants of tourism demands in Malaysia are addressed effectively by the academicians and researchers.